Retail Diversity for Diet Diversity - Shopping Practices Household Survey - Wertheim-Heck, Sigrid C.O.; Raneri, Jessica Evelyn (Bioversity International, 2020)
Households within the field sites were randomly selected and administered a survey to capture data on their food shopping practices and preferences and how that related to food safety concerns and practices.